HPV Vaccination Coverage Rate in a Rural Area: An Observational, Retrospective, and Cohort Study - Lara Colomé-Ceballos; Josep Lluís Clua-Espuny; José Fernández-Sáez; Concepción Ceballos-García; Natàlia Andrés-Cubells; Maria Jesús Pla-Farnós (Vaccines, 2022)
In order to reduce the incidence and mortality rate of cervical cancer, the World Health Organization (WHO) declared the Global Strategy Goal for 2030, advocating for reaching a vaccination coverage rate of >90% against human papillomavirus for girls by the age of 15 years. The main objectives of this study were (1) to determine the papillomavirus vaccination coverage among women 15–40 years old and (2) to identify the at-risk subgroups and possible barriers to achieving WHO’s 2030 goal. Multicentre, observational, retrospective, and community-based cohort studies were conducted on women from a rural area in southern Catalonia until 31 December 2021. A total of 23,136 women were included, with a mean age of 26.6 (SD = 5.6) years. The average dose number was 1.7 (SD = 0.7). The results showed overall vaccination coverage of 17.4% among the target women. This coverage was unequal across regions (16.6–24.5%, p < 0.001), primary healthcare teams (15.5–24.3%, p < 0.001), and age groups (56.7% (15–19-year-olds) vs. 3.8% (35–40-year-olds), p < 0.001), related to accessibility to vaccination and economic–geographical indicators. Clinical practice guidelines on screening individuals at risk in terms of vaccination access and public vaccination protocols should be implemented in order to improve the vaccination coverage rate.